2001
DOI: 10.1034/j.1399-302x.2001.016002113.x
|View full text |Cite
|
Sign up to set email alerts
|

Subgingival strains of Candida albicans in relation to geographical origin and occurrence of periodontal pathogenic bacteria

Abstract: Clonal diversity of subgingival yeast strains was determined in relation to geographical location and coexistence of selected periodontal pathogenic bacteria. A total of 60 dental patients from Finland, the United States and Turkey each contributed five Candida albicans isolates. C. albicans isolates were serotyped using slide agglutination and genotyped using polymerase chain reaction (PCR) amplification and a random sequence primer. In general, each study subject yielded C. albicans isolates belonging to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0
22

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 33 publications
3
22
0
22
Order By: Relevance
“…In dental practice, chronic atrophic candidosis (denture stomatitis) is perhaps one of the most frequently encountered oral Candida infections (Wilson, 1998). There has also been an increasing interest in the presence of yeasts in infected periodontal pockets and their possible role in the pathology of different forms of periodontitis (Slots et al, 1988;Zambon et al, 1990;Rams and Slots, 1991;Dahlén and Wickström, 1995;Hannula et al, 1997Hannula et al, , 2001 …”
Section: Oral Yeast Infectionsmentioning
confidence: 99%
“…In dental practice, chronic atrophic candidosis (denture stomatitis) is perhaps one of the most frequently encountered oral Candida infections (Wilson, 1998). There has also been an increasing interest in the presence of yeasts in infected periodontal pockets and their possible role in the pathology of different forms of periodontitis (Slots et al, 1988;Zambon et al, 1990;Rams and Slots, 1991;Dahlén and Wickström, 1995;Hannula et al, 1997Hannula et al, , 2001 …”
Section: Oral Yeast Infectionsmentioning
confidence: 99%
“…Although the presence of yeasts was a striking feature of the subgingival plaque samples from some AIDS patients, follow-up studies confirming these preliminary data have been lacking (11,27,28,32). The present investigation sought to begin to determine any association between the recovery of yeasts and the presence of advanced periodontal lesions.…”
mentioning
confidence: 99%
“…Yeast species in the subgingival tissue of AIDS patients may also be the source of disseminated candidosis. The most recent study performed by Hannula et al (11) on isolation of subgingival yeasts reported that the mean proportion of total microbiota was higher for C. albicans-positive samples than for C. albicans-negative samples from selected subjects, indicating the need for further analysis to determine the relationship between subgingival occurrence of C. albicans and periodontal diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Se ha sugerido que el uso de antibióticos de amplio espectro puede desencadenar sobreinfecciones con levaduras en la bolsa periodontal como resultado del disturbio que causan en la homeostasis de la microflora habitual (7). En la cavidad bucal, las levaduras colonizan lengua, paladar, mucosa oral y saliva (8). Específi-camente, la Candida Albicans se ha encontrado en gran cantidad en bolsas periodontales (7,1-26,9%) de pacientes con periodontitis crónica (2-4, 9-11).…”
Section: Introductionunclassified